A STUDY OF THE IMPLEMENTATION OF TEACHING SPEAKING OF PRIMARY SPEAKING CLASS AT SMART ILC PARE KEDIRI - Sutrimo, Sutrimo (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2020)
The main objective of this study is to describe how the teaching of Primary Speaking class at SMART ILC. The researcher limits this study only to find and then describe; the implementation, the responses of the students, the result of the students, and the evaluation of the students after joining Primary Speaking class at SMART ILC. This research used descriptive qualitative approach as a research design. The subject was Primary Speaking students. The methods used in collecting data were interview, observation, field note and documentation. The data analysis was based on three concurrent flows of activities, they were: data reduction, data display, and verification. The result of this study shows that syllabus, lesson plan, materials, method, technique, and media of teaching were available. The curriculum was not necessary for non-formal education to have it. The resrponses which came from students were various. They were active, responsive, nervous, but they felt enjoyable. The result of students after joining the class was FAIR. And the evaluation that the students gave according to the documentation was GOOD.